2014
DOI: 10.1515/cclm-2013-0693
|View full text |Cite
|
Sign up to set email alerts
|

NGAL, L-FABP, and KIM-1 in comparison to established markers of renal dysfunction

Abstract: Urinary NGAL and L-FABP proved to be promising candidates for detecting injuries of the renal tubular system over a broad range of clinical conditions. L-FABP showed a better diagnostic performance and a lower interference by leukocyturia and hematuria than NGAL. Both markers may serve as sensitive tissue injury markers in addition to the established markers of renal functional impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 28 publications
1
34
0
Order By: Relevance
“…[32][33][34] Also inflammatory comorbidities such as urinary tract infections and sepsis can serve as confounders, as inflammation results in systemic release of NGAL derived from other organs as well. 35 Moreover, even though urinary NGAL levels were increased in preterm neonates with sCrdocumented AKI, NGAL levels did not predict AKI prior to its development. 36 In general, these biomarkers represent upregulated protein levels during renal injury which are derived from specific segments of the nephron.…”
Section: Discussionmentioning
confidence: 95%
“…[32][33][34] Also inflammatory comorbidities such as urinary tract infections and sepsis can serve as confounders, as inflammation results in systemic release of NGAL derived from other organs as well. 35 Moreover, even though urinary NGAL levels were increased in preterm neonates with sCrdocumented AKI, NGAL levels did not predict AKI prior to its development. 36 In general, these biomarkers represent upregulated protein levels during renal injury which are derived from specific segments of the nephron.…”
Section: Discussionmentioning
confidence: 95%
“…These new variables could include circulating or urine biomarkers, systemic or kidney hemodynamics, and imaging markers. Neutrophil gelatinaseassociated lipocalin, interleukin-18, kidney injury molecule-1, L-fatty acid binding protein, and cystatin C are the most-known relevant biomarkers that have been used in AKI risk prediction [25][26][27]. Recent advances in methodologies to assess physiological biomarkers reflecting systemic or kidney hemodynamics were lately reviewed by the Acute Dialysis Quality Improvement (ADQI) workgroup [28].…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil gelatinase-associated lipocalin (NGAL) and kidney injury molecule-1 (KIM-1) are promising candidates to detect kidney injuries in the early stages. These proteins are expressed by renal tubules, and clinical investigations have shown that they are massively expressed in cases of AKI in both adults and children [ 203 , 205 , 207 , 208 , 213 217 ]. NGAL concentrations seem to correlate with the severity/stage of CKD [ 204 ].…”
Section: Kidney Function and Its Impact On Drugs In Pediatric Patientmentioning
confidence: 99%